92.1k views
1 vote
How do you solve the highlighted problem?

How do you solve the highlighted problem?-example-1

1 Answer

4 votes
these just teest your understanding or memory on the exponential rules
the rules for each are as follows
a.
(x^m)(x^n)=x^(m+n)
b.
(x^m)/(x^n)=x^(m-n)
c.
x^(-m)= (1)/(x^m)
d.
(ab)^m=(a^m)(b^m) and
(x^m)^n=x^(mn)


so

a.
(x^3)(x^(-2))=x^(3-2)=x^(1)=x
b.
(y^5)/(y^(-2))=y^(5-(-2))=y^(5+2)=y^(7)
c.
4^(-1)= (1)/(4^1)= (1)/(4)
d.
(4x^2)^3=(4^3)((x^2)^3) and
(x^2)^3=x^(2*3)=x^(6)
result is
64x^6
User Manushka
by
6.1k points